Enhancement of library services by Design Thinking methods in the Library of Horlivka State Pedagogical Institute for Foreign Languages - Ielizaveta Bielitska (2019)
This paper proposes the usage of untraditional problem-solving methods of Design Thinking in the Academic Library of Horlivka Institute for Foreign Languages in the city of Bakhmut, Ukraine. The thesis introduces the theoretical aspect of “Design Thinking” approach through its methodology and principles, and the practical aspect through the student´ project. It starts with the history of Design Thinking in the early 60s and continues with its modern understanding and methods. Further it presents the library problem field and the role of Design Thinking in enhancing the library services. Following the general structure of Design Thinking methods and the “Toolkit for libraries” designed by IDEO the team of students (design team) defines the library service problems: short opening hours, bad space organization and lack of library events. Further the design team conducts ideation sessions, where students create proper ideas in order to solve the problems. After the ideation sessions the design team does the prototyping. With the help of sketches and event scenarios students can test their ideas in practice. The successful completion of the test phase is determined by the positive feedback.
Keywords: Design Thinking; IDEO Toolkit; design team; Design Thinking challenge; academic library; prototyping; Design Thinking methods; customer journey